2007
DOI: 10.1177/104063870701900406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tests for Detection of Bovine Viral Diarrhea Virus in Diagnostic Samples

Abstract: Abstract. Currently, a variety of tests are used to detect bovine viral diarrhea virus (BVDV) in persistently infected (PI) cattle. These tests include immunohistochemical staining (IHC), antigen capture enzyme-linked immunosorbent assay (ACE), virus isolation (VI), and reverse transcription-polymerase chain reaction (RT-PCR). However, a lack of methods standardization could compromise the ability to consistently identify animals infected with BVDV. This study evaluated the diagnostic proficiency of current me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
0
26
0
5
Order By: Relevance
“…RT-PCR and IHC correctly identified around 85% BVDV positive samples while VI using serum showed poor consistency and lowest level of agreement. The finding of this study suggested a need for standardization of test methods (Edmondson et al, 2007).…”
Section: Genotypingmentioning
confidence: 77%
“…RT-PCR and IHC correctly identified around 85% BVDV positive samples while VI using serum showed poor consistency and lowest level of agreement. The finding of this study suggested a need for standardization of test methods (Edmondson et al, 2007).…”
Section: Genotypingmentioning
confidence: 77%
“…Virus isolation and inoculation of cultured cells, followed by identification of the viral isolate by immunofluorescence or immunoperoxidase monolayer assay, are considered to be the gold standard for detection of BVDV [10]. If titers in the samples material are high enough, it is even possible to quantify the amount of virus by titration in susceptible cell lines [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, care must be taken, as with increasing pool size the danger of false negative results increases when assay sensitivity and specificity are too low [13]. On the other hand, pooling too few samples unnecessarily keeps the examination costs high [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous methods have been developed to diagnose both persistent infection and acute or transient infection with BVDV. These include antigen-capture (AC) enzyme-linked immunosorbent assay (ELISA), immunohistochemical (IHC) testing, gel-based reverse-transcription (RT), real-time polymerase chain reaction (PCR), and virus isolation using WBC lysates, tissues, or whole blood in cell culture [64,65]. Also, there are numerous serological methods of measuring seroconversion from acute infection, including ELISA and viral neutralization tests in cell culture.…”
Section: Bovine Viral Diarrhea Virusmentioning
confidence: 99%